REPROGRAMMING OF SPLENIC MONONUCLEAR PHAGOCYTE PHENOTYPE DURING MODELING OF SYSTEMIC JUVENILE IDIOPATHIC ARTHRITISIN WISTAR RATS (Сеченовский вестник, 2017)
Purpose. This study is devoted to the evaluation of the number of splenic alternatively activated (M2, CD163+) macrophages and other mononuclear phagocytes after arthritis development in a model of systemic juvenile arthritis in Wistar rats (with and without modiﬁcation by doxycycline or dexamethasone). Methods. Cell phenotypes were assessed by ﬂow cytometric analysis. Percentages of classically-activated phagocytes were estimated (M1, CD163-). Results. The indexes of dominating phenotypes are assessed for spleen (no signiﬁcant differences in animal groups). In comparison we demonstrate indexes for the blood mononuclear phagocytes (signiﬁcant changes were observed). Nevetherless, we have demonstrated phenotypical changes of splenic phagocyte population at whole. Conclusions. Redistribution of the tissue alternatively-activated cells of phagocyte population in spleen was found to be signiﬁcantly different in animal groups with doxycycline and dexamethasone administration.